Investimento parental de mãe surda e mãe ouvinte e seus bebês ouvintes - ALBUQUERQUE, Raphaella Duarte Lopes de (Universidade Federal do Pará, 2014)
The human baby is prematurely born compared to the primate pattern, and this physical immaturity creates a longer duration of dependence and intensification of parental adult care. This study was based on Heidi Keller’s theoretical framework of Parental Investment Model, which assumes six parental systems, evolved in response to adaptive problems faced by our ancestors. The parental systems represent investments that differ in respect of energy, time, attention and tone emotional targeted to the baby. The proposed parental systems are systems of primary care, system of body contact, system of body stimulation, system of object stimulation, face-to-face and narrative envelope. The predominance of one of these systems will depend on the culture. However, investigations conducted up to now included only typical dyads. In addition, there are no longitudinal studies focusing on the characteristics of parental systems developed between dyads whose sensory channels used to initial interchange differ, for instance deaf mothers and their hearing infants. This study investigated the parental systems prioritized by a deaf mother and a hearing mother in relation to their hearing babies, as well as the characteristics of instancies of interaction between a deaf mother - hearing infant. The mothers were primiparous, with higher educational level, and their ages were 34 and 36 years old, resident in Belém, and their infants were male. Footage was shot, weekly until three months, and from two to two weeks until six months in bath situations, changing clothes, feeding and free play from the three months, at mothers’ home. The parental systems were recorded at an interval of ten seconds, and then recorded the mother and infant general behaviors by second instancies of interaction. The results indicated that the deaf mother prioritized object stimulation, and body contact. Hearing mother prioritized body stimulation, body contact, and face-to-face. Besides the differences in stimulation type prioritized by each mother, the body contact was qualitatively different between them. The results suggest a model autonomous-relational for dyads. The analysis of interactions deaf mother - hearing infant indicated that mother begins the most interactions during the study period, and suggests that the dyad showed changes in interactions throughout the baby development. However, it emphasizes the necessity for more studies to increase the knowledge of atypical dyads peculiarities, such as re-defining the categories and searching for new parental systems.